Comparison of Radiotherapy Plans for Esophageal and Lung Tumors Using 3DCRT and IMRT Technology - محمود, أيهم; شبول, شجاع (Latakia University Journal -Medical Sciences Series, 2020)
Treatment plans were studied for patients with lung and esophageal tumors, patients were imaged using CT-Scan (PHILIP TYPE) and the images were sent to the Treatment Planning System-TPS (ECLIPS type), the system in which the doctor identified the tumor and at-risk organs. Conventional 3D-Conformal Radiotherapy (3DCRT) and Intensity-Modulated Radiotherapy (IMRT) plans were created for the same patients. Treatment plans were compared according to the Dose Volume Histogram (DVH). It was observed that the radiation dose distribution of radiotherapy plans using IMRT technique better suited to tumor size (CTV) and protecting more organs surrounding the tumor, but it takes longer than 3DCRT technology. Therefore it is necessary to determine which patients should be treated with one technique (3DCRT or IMRT) or another technique depending on the full dose given to CTV and the time it generally takes.